Effect of heat generation on mixed convection of micropolar Casson fluid over a stretching/shrinking sheet with suction - Rahimah, Jusoh; Roslinda, Nazar (IOP Publishing, 2019)
The problem of mixed convection involving the micropolar Casson fluid over a stretching/shrinking sheet is scrutinized in this study. The sheet is considered permeable with the inclusion of suction. The effect of heat generation is also taken into account. A set of suitable similarity variables is employed to reduce the governing partial differential equations to the ordinary differential equations. The built in bvp4c function in Matlab is utilized to solve the resulting ordinary differential equations. Elucidation of numerical results for the skin friction coefficient, Nusselt number and temperature profiles are presented through graphs for a certain range of governing parameters. The existence of non-unique solutions (dual solutions) are also discovered in this study. Final conclusion has been drawn on the effect of variations in suction parameter, Biot number and heat generation parameter and on the flow and heat transfer characteristics. Stability analysis reveals that the first solution is stable while the second solution is unstable.